Effectiveness of Vitamin D and Vitamin B Supplementation Therapy in Diabetic Neuropathic Pain Standard Therapy - Rizaldy T. Pinzon; Yohana R. T. D. Christi (Universitas Padjadjaran, 2020)
The chronic complication from diabetes mellitus (DM) is painful diabetic neuropathy, and the treatment with standard therapy is inefficient. Furthermore, vitamin B combination is effective as a neuropathy treatment due to nerve repair acceleration by enhancing regeneration and restoring function, while individuals with type 2 DM are inseparable from vitamin D deficiency. This study aimed to measure diabetic neuropathy pain reduction in patients with type 2 DM by administration of additional vitamin D to standard therapy. This was a quasi-experimental study employing non-equivalent control group method on 77 patients selected using consecutive sampling at Bethesda Hospital Yogyakarta between December 2019 and February 2020. In addition, the subjects consisted of 48 men and 29 women, and were divided into 4 therapy groups executed within 1–3 months comprising (I) symptomatic therapy only; (II) symptomatic combination therapy with vitamin B; (III) symptomatic combination therapy with vitamin D; and (IV) symptomatic combination therapy with vitamin B-vitamin D. The pain assessment employed Visual Analogue Scale (VAS) prior and after administration, and demographic characteristics data between the 4 groups lacked noteworthy differences. The results indicated decreased pain intensity after therapy with the mean VAS in group I from 53.36±14.65 to 42.27±17.16, group II from 50.56±12.11 to 13.89±14.61, group III from 50.77±15.98 to 19.23±18.09, and group IV from 54.55±16.35 to 7.27±6.47. However, group administered with symptomatic combination therapy with vitamin D revealed higher significant improvement, while substantial pain intensity reduction was indicated from symptomatic therapy combined with vitamin B and vitamin D.Keywords: Combination of vitamin D, pain intensity, painful diabetic neuropathy Efektivitas Pemberian Terapi Tambahan Vitamin D dan Vitamin Bpada Terapi Standar Nyeri Neuropati DiabetikAbstrakNeuropati diabetik merupakan salah satu komplikasi kronis yang sering terjadi dari penyakit diabetes melitus (DM). Pengobatan neuropati diabetik dengan terapi simptomatik hingga sekarang belum mencapai target. Vitamin B kombinasi efektif sebagai pengobatan neuropati karena mempercepat perbaikan saraf dengan meningkatkan regenerasi saraf dan memulihkan fungsi saraf. Pasien DM tipe 2 tak lepas dari keadaan defisiensi vitamin D. Penelitian ini bertujuan untuk mengukur penurunan nyeri neuropati diabetik pada pasien DM tipe 2 yang diberi terapi tambahan vitamin D terhadap terapi standar. Penelitian ini merupakan penelitian quasi-experimental dengan metode non equivalent control group kepada 77 pasien yang terpilih berdasarkan consecutive sampling di Rumah Sakit Bethesda Yogyakarta pada bulan Desember 2019–Februari 2020.Subjek dibagi menjadi 4 kelompok pemberian terapi yaitu kelompok yang diberi (1) terapi simptomatik saja, (2) terapi simptomatik kombinasi vitamin B, (3) terapi simptomatik kombinasi vitamin D, dan (4) terapi simptomatik kombinasi vitamin B-vitamin D. Pemberian terapi dilakukan dalam waktu 1–3 bulan. Penilaian nyeri menggunakan Visual Analogue Scale (VAS) sebelum diberikan terapi dan setelah pemberian terapi. Subjek terdiri dari 48 orang laki-laki dan 29 orang perempuan. Data karakteristik demografi di antara 4 kelompok tidak memiliki perbedaan yang bermakna. Hasil penelitian menunjukkan adanya penurunan intensitas nyeri dengan rata-rata VAS kelompok I sebelum terapi 53,36±14,65 menjadi 42,27±17,16 setelah terapi, kelompok II dari 50,56±12,11 menjadi 13,89±14,61, kelompok III dari 50,77±15,98 menjadi 19,23±18,09, dan kelompok IV dari 54,55±16,35 menjadi 7,27±6,47. Kelompok dengan terapi tambahan vitamin D menunjukkan perbaikan nyeri yang lebih signifikan. Penurunan intensitas nyeri neuropati diabetik secara signifikan ditemukan pada pemberian terapi simptomatik yang dikombinasikan dengan vitamin B dan vitamin D. Kata kunci: Intensitas nyeri, kombinasi vitamin D, nyeri neuropati diabetik